Creative Industries and Regional Economic Growth: Time Series Evidence from Aceh, Indonesia - Hasan, Amiruddin; Nurhasanah, Nurhasanah; Mardhani, Martahadi; Aswadi, Khairul (Journal of Economics Education and Entrepreneurship, 2023)
This study aims to provide an overview of the role of the creative industries in driving regional economic growth in Aceh, Indonesia. This study uses secondary data from official government agencies observed from 2011 to 2016. We use the Ordinary Least Squares (OLS) estimation to estimate the impact. The results showed that, partially, employment in the creative industries had a positive and significant effect on economic growth, while the value of exports in the creative industries had no significant effect. However, simultaneously these two variables have a positive and significant influence on economic growth. This finding implies the importance of stakeholder involvement to strengthen the performance and contribution of the creative industry in the future.